Marketing Innovation And Sustainable Competitive Advantage: A Case Of Selected Manufacturing Small And Medium Enterprises In Central Region Of Ghana - Mensah, I. (University of Ghana, 2017)
Global business trends such as globalisation, technology revolution and trade liberalisation have affected operations of Small and Medium sized Enterprises (SMEs) across the global. In developing countries including Ghana, the global trends have affected operations of SMEs in the domestic markets such as Central region (an administrative region in Ghana). Studies have therefore been done in developing countries such as Ghana regarding how SMEs have responded to these compelling global trends especially with innovative marketing activities. However, findings from Ghana appear contrary to what exist in developed countries to the effect that SMEs in Ghana are not innovative. Evidently, studies in Ghana generalised the context of innovation and did not address any specific type of innovation. To address this gap, this study formulated objectives to investigate the effect of marketing innovation on sustinable competitive advantage using Resource Based Theory and Dynamic Capability Theory. This quantitative study uses a survey research design and a semi-structured questionnaire as a primary data collection instrument. Stratified and simple random sampling techniques were used to sample three hundred and fifty manufacturing SMEs in Central Region for the study. This study found that SMEs in Central region are innovative in terms of marketing. This study results further shows that integration of both marketing resources and capabilities are key to develop marketing innovation which lead to SCA. The study recommends that SME managers and owners should prioritize their marketing competence in product designs, promotion and retailing innovations. Again, government as a matter of urgency must develop targeted policies to bridge the information gap between SMEs and research institutions such as universities in order to improve the capabilities of SME managers and owners.
Thesis (MPhil)
Keywords: Marketing Innovation; Sustainable Competitive Advantage; Manufacturing Small Enterprises; Manufacturing Medium Enterprises; Ghana